Expanding Language Development In Preschool Age Children - Afitriani Afitriani; Ibnu Fari Nugroho; Undo Baliang (Universitas Muhammadiyah Surabaya, 2020)
Abstract. Important language knowledge taproot during school. Preschool Classroomcurriculum can help with language development through various exploration activities,activities that are guided by the teacher, and routine activities. Teachers ' understanding of the potential to expand language development in all the preschool curriculum priests provides many opportunities for children to see the language being used. Specific teaching strategies that are effective in supporting language development include asking questions, buffering language, mediation, and conflict resolution. Activities that combine books, poetry and songs encourage children to develop receptive and expressive knowledge in written language and to develop their receptive and expressive knowledge in spoken language. Keywords: Development; language; preschoolers